The Role of Fintech in Promoting Financial Inclusion: Evidence from Latin America - Rivera P, Mauricio; Balanzategui G, Rosalina; Dávalos M, Eduardo; Juelas C, Patricio; Mino, Juan Pablo (Journal of Posthumanism, 2025)
Financial technology innovations, known as Fintech, are a fundamental tool for advancing financial inclusion by offering innovative and accessible solutions to individuals and businesses previously excluded from traditional financial services. This role is particularly relevant in Latin American countries, where geographic dispersion and a lack of financial literacy limit financial access. This study aims to analyze the impact of financial technology on financial inclusion in Latin American countries by employing a balanced panel data model. The analysis uses cross-sectional data from the years 2011, 2014, 2017, and 2021. Fintech is proxied by fixed broadband subscriptions (per 100 people), while financial inclusion is captured through the use of digital payments, along with other variables related to access and usage of financial services and selected macroeconomic control variables. The main findings highlight the importance of digital infrastructure in facilitating formal access to the financial system, particularly through account ownership and savings capacity, though not through access to credit.